2019
DOI: 10.1021/acsnano.9b03982
|View full text |Cite
|
Sign up to set email alerts
|

Lysozyme-Assisted Photothermal Eradication of Methicillin-Resistant Staphylococcus aureus Infection and Accelerated Tissue Repair with Natural Melanosome Nanostructures

Abstract: Patients often face the challenge of antibiotic-resistant bacterial infections and lengthy tissue reconstruction after surgery. Herein, human hair-melanosome derivatives (HHMs), comprising keratins and melanins, are developed using a simple “low-temperature alkali heat” method for potentially personalized therapy. The mulberry-shaped HHMs have an average width of ∼270 nm and an average length of ∼700 nm, and the negatively charged HHMs can absorb positively charged Lysozyme (Lyso) to form the HHMs-Lyso composi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(50 citation statements)
references
References 49 publications
1
49
0
Order By: Relevance
“…Moreover, mild photothermal effects (~43°C) reported in recent studies can not only greatly enhance the proliferation of MSCs but also promote osteogenesis. [171][172][173][174][175] This is good news for bone tumor therapy. The mild photothermal effect was shown to stimulate and accelerate in vitro and in vivo osteogenesis.…”
Section: Discussion and Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, mild photothermal effects (~43°C) reported in recent studies can not only greatly enhance the proliferation of MSCs but also promote osteogenesis. [171][172][173][174][175] This is good news for bone tumor therapy. The mild photothermal effect was shown to stimulate and accelerate in vitro and in vivo osteogenesis.…”
Section: Discussion and Perspectivementioning
confidence: 99%
“…Melanoma treatment requires the complicated removal of tumor tissue and cutaneous defect repair. [173][174][175] Oral tumors simultaneously destroy the facial bone. In clinical treatment, doctors remove oral tumor tissues along with the surrounding jawbone then collect the patient's fibula and use it to replace the jawbone with vascular anastomosis.…”
Section: Discussion and Perspectivementioning
confidence: 99%
“…The extraction method includes centrifugation with water or washing with salts [49]. In two different studies, melanin has also been successfully extracted from black sesame seeds and human hair [59][60][61]. However, it is obvious that the acquisition of melanin from different biological sources has the disadvantage of inherent variations in the physicochemical properties of the biopigments, something that increases the need of a standardized extraction and purification method.…”
Section: Natural Versus Synthetic Sourcesmentioning
confidence: 99%
“…In fact, PTT can also act synergistically with antimicrobial-NP in order to inhibit bacterial growth, disrupt their membrane and offer an enhanced antibacterial effect [228]. Taking this into account, Li et al, reported a novel PDA composites that showed promising antibacterial properties against methicillin-resistant Staphylococcus aureus (MRSA) [60]. MRSA eradication was achieved thanks to the synergistic effect of PTT and Lysozyme (Lyso) assisted antibiotic action [229].…”
Section: Antibacterial Infectionsmentioning
confidence: 99%
“…Therefore, nanozymes with peroxidaselike activity used together with H 2 O 2 can overcome abovementioned problems including unsatisfactory antibacterial effect under low concentration of H 2 O 2 and unwanted side effects under high concentration of H 2 O 2 , exhibiting great potential in further treatment of wound infection. More importantly, extra characteristics of nanozymes, such as defect-rich adhesive, photodynamic, photothermal, and sonodynamic functionalities, can highly enhance their antibacterial activities both in vitro and in vivo (Cao et al, 2019;Li J. et al, 2019;Li S. et al, 2019;Sun et al, 2020;Wang et al, 2020b). Although promising, the intrinsic components of currently reported nanozymes usually limit their further biomedical usages and clinical transformation.…”
Section: Introductionmentioning
confidence: 99%